IMPROVING ENGLISH SPEAKING SKILLS THROUGH SMALL GROUP DISCUSSION - Lina Susanti; Mutmainnah Mustofa; Fatimatus Zahroh Fatimatus Zahroh (Journal of English for Academic and Specific Purposes (JEASP), 2021)
This research is aimed at inquiring the use of small group discussions in the improvement of speaking skills studied in classroom action research (CAR). The population of the research was the eighth-grade students of SMPN 2 Curug consist of thirty students. The researchers used one class as a control group. Based the result of this study, the researchers implemented the action in two cycles; every cycle consists of planning, acting, observing and reflecting. The first is planning, the researchers identified a problem. The second is acting, the researchers collected and analysed the data. The third is observing, in this stage the researchers developed a plan to make change and implemented these changes. This cycle reflects the components of action research. It is critical to consider the impact of the changes made when reflecting. The result of this research is the mean score of students on the speaking test before carrying out the Class Action Research (CAR) is 57,5 for pretest and post-test 64,7 in the first cycle, this is the student’s treatment. And in the second cycle 70,6 after using small group discussion. It means that the mean score of the post test is greater than the pre-test. Thus, this research that using small group discussion can improve students’ speaking ability for the eighth-year students of SMPN 2 Curug.